Dalla tavoletta al tablet: metodi classici e nuove tecnologie a confronto per l'Assiriologia. - Surdi, Mirko (Archeomatica, 2017)
Computer sciences are applied more frequently in Humanities and the present research is an example of the application of new technologies to Assyriology, i.e. the discipline studying the civilizations of ancient Mesopotamia. Photogrammetry, structured-light scanner and Reflectance Transformation Imaging were employed together in order to demonstrate how they can improve the fruition and the study of cuneiform tablets, or clay supports where "cuneiform signs” were impressed. The corpus of texts used for this research is represented by the collection of the Bank of Italy, at present the largest and most numerous collection of cuneiform tablets in Italy.